Federalism in Russia: Current State and Emerging Trends - M. Salikov (BRICS Law Journal, 2020)
The article considers the phenomenon of federal relations in modern Russia from a theoretical and normative point of view. Studying related categories, such as federalism, federation and federal system, the author comes to the conclusion that it is federal relations, which by their nature are purely legal relations, are the core of any federal system. It is the analysis of the dynamics of development of these relations that shows the viability of a particular federal system. Using the concept of systems theory, the author reveals the structure of federal relations, which includes their subjects, objects and content. In turn, the content of federal relations can be revealed using the principles of both the horizontal and the vertical separation of powers. In this regard, not only normative regulation (the Constitution, federal and regional laws), but also judicial practice are of great importance: namely, decisions of the Constitutional Court of the Russian Federation, which handed down a significant number of decisions revealing the essence of federal relations in specific cases and resolving existing problems. The development of the federal system, and, consequently, the actual federal relations can be traced in examples of an institutional and regulatory nature. Vivid examples of this development are structural changes in the federal system associated with the formation of a new constituent entity of the federation and the adoption of a new constituent entity in the federation. Such examples have occurred in modern Russia, although in the case of the adoption of new entities in the current regulatory framework, certain problems are found that should be eliminated by making appropriate amendments to the law governing the procedure for such adoption. The COVID-19 pandemic, unfortunately, has affected virtually every nation in the world. The relationship between the federal center and the constituent entities of the federation in such an extraordinary situation has been affected too and has undergone certain changes. Their analysis cannot but lead to a correction of the normative regulation of federal relations in the event of similar situations in the future. Amendments to the Constitution of the Russian Federation have affected a large layer of public relations. Federal relations are no exception, since the “Federated Structure” section of the Constitution includes a number of rather interesting changes.